Quantifying Nutrient Ratios as Soil Fertility and Health Indicators across a Hydrosequence Transect in North Musi Rawas, South Sumatra - Pulunggono, Heru Bagus; Adiani, Ditta Rahma; Nurazizah, Lina Latifah; Chahyahusna, Affan; Iskandar (Faculty of Agriculture, Tompotika Luwuk University, 2024)
Since the modern soil assessment focus is currently moving towards “soil health”, it is important to align the Basic Cation Saturation Ratio/BCSR of soil fertility evaluation with this term, yet no research conducted its application in tandem with CNP stoichiometries, nor vice versa. This study evaluated soil nutrient ratios across a hydrosequence transect in North Musi Rawas Regency, the lowland area of eastern Sumatra using Basic Cation Saturation Ratio/BCSR and CNP stoichiometries as potential soil health indicators. By integrating international and national/Indonesian BCSR framework and globally recognized CNP stoichiometry criteria, this study found that all soils experienced cation deficiencies, particularly in the upper soil depth (0–30 cm), alongside low phosphorus (P) and potassium (K) availabilities and their imbalances with C and N in deeper layers (30–60 cm). Cation ratios were observed to decline closer to the Merang River but increased with sampling depth. Additionally, wetter, gleyed soils exhibited greater cation imbalances while maintaining relatively balanced CNP stoichiometries. This study proposes an integrated multi-proxy approach combining BCSR and CNP stoichiometries as a cost-effective method for assessing soil fertility and health by addressing nutrient imbalances.